Model Pembelajaran Student Facilitator And Explaining Untuk Meningkatkan Hasil Belajar IPA di Sekolah Dasar - Gilang Maulana Jamaludin; Arita Marini (Universitas Majalengka, 2022)
This study aims to determine the increase in science learning outcomes through the application of the Student Facilitator and Explaining learning model to fifth grade students of SD Negeri Padasuka II, Sumedang Utara District, Sumedang Regency. The approach used is a qualitative approach to the type of research that is classroom action research (CAR). The research location is SD Negeri Padasuka II, North Sumedang District, Sumedang Regency. Data collection techniques are observation, documentation, and tests. The results showed that the science learning outcomes for fifth grade students of SD Negeri Padasuka II, North Sumedang District, Sumedang Regency were in the less category, after being treated, namely the application of the Student Facilitator and Explaining learning model in improving science learning outcomes for fifth grade students at SD Negeri Padasuka II District North Sumedang Sumedang Regency is in the good category. So there is an increase in student learning outcomes.